Analysis of Research Skill in Understanding Research Method to Prospective Teacher at Islamic Elementary School - Irfan, Irfan; Prastowo, Andi; Fatonah, Siti; Malahati, Fildza; Jannati, Putri; Nurjanna, Ummi Atya (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
At both the secondary and tertiary education level, Indonesia's low research ability is a sign which prospective teachers have not demonstrated the best research abilities. The purpose of this study was to identify skills in understanding research methodology for prospective teachers at islamic elementary school. The research method used is a case study using a qualitative approach. The data used are primary data and secondary data, primary data obtained through observation and interviews with 23 prospective teachers in class VI while secondary data researchers obtained from supporting reference documents in the form of relevant articles and books. Data validation is in the form of data triangulation with three classifications, namely analysis, interpretation and conclusion. The results of the findings of this study are the ability to observe problems that will be identified later. Achievement with this indicator has not shown optimal achievement. The ability to interpret the problem with the formulation of the problem. The achievement of this indicator is not optimal. The ability to group variables to formulate hypotheses. The achievement of this indicator has shown optimal ability. The ability to take samples to make research designs, the achievement of this indicator has experienced optimal achievement. The ability to collect, analyze and compare data, the ability to collect and analyze data has been optimally achieved because it is supported by observational data such as the spontaneity of prospective teachers when given assignments or questions and answers in class regarding the indicators contained in this study while for the ability to observe problems , formulating problems and comparing data that has not been optimally achieved due to the lack of reading literature and the condition of prospective teachers who take part in online learning because there is a task of introducing school fields (PLP) outside the campus so that the understanding of prospective teachers is not optimal.